2001
DOI: 10.1037/0893-3200.15.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Maternal disclosure of mothers' HIV serostatus to their young children.

Abstract: Mothers' disclosure of their HIV serostatus to their noninfected young children and factors associated with disclosure were investigated among 135 families. Overall, 30% of the mothers had personally disclosed their serostatus to their children. Mothers who disclosed reported higher levels of social support in their lives than mothers who did not disclose. Children whose mothers had disclosed to them displayed lower levels of aggressiveness and negative self-esteem compared to children whose mother had not dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
161
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(177 citation statements)
references
References 18 publications
9
161
7
Order By: Relevance
“…Various rates of disclosure of parental HIV/AIDS to children have been reported, ranging from 0% (Esposito et al, 1999) to 74% (Armistead et al, 1997(Armistead et al, , 2001Bauman et al, Camacho et al, 2002;Forsyth et al, 1996;Lee & Rotheram-Borus, 2002;Murphy et al, 2001;Murphy, Marelich et al, 2002;Nagler et al, 1995;Niebuhr et al, 1994;Nostlinger et al, 2004;Ostrom et al, 2006;Pilowsky et al, 1999;Rotheram-Borus et al, 1997;Schrimshaw & Siegel, 2002;Shaffer et al, 2001;Sowell et al, 1997;Tompkins et al, 1999;Wiener et al, 1998), and likely depend on such factors as child age, disease progression, quality of the parent-child relationship, and general cultural influences on disclosure-and child-related beliefs. Although parents commonly cite protection from distress as a major reason for withholding illness-related information from children, clinical observation indicates that children typically have some sense that something is wrong anyway (Melvin, 1996).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Various rates of disclosure of parental HIV/AIDS to children have been reported, ranging from 0% (Esposito et al, 1999) to 74% (Armistead et al, 1997(Armistead et al, , 2001Bauman et al, Camacho et al, 2002;Forsyth et al, 1996;Lee & Rotheram-Borus, 2002;Murphy et al, 2001;Murphy, Marelich et al, 2002;Nagler et al, 1995;Niebuhr et al, 1994;Nostlinger et al, 2004;Ostrom et al, 2006;Pilowsky et al, 1999;Rotheram-Borus et al, 1997;Schrimshaw & Siegel, 2002;Shaffer et al, 2001;Sowell et al, 1997;Tompkins et al, 1999;Wiener et al, 1998), and likely depend on such factors as child age, disease progression, quality of the parent-child relationship, and general cultural influences on disclosure-and child-related beliefs. Although parents commonly cite protection from distress as a major reason for withholding illness-related information from children, clinical observation indicates that children typically have some sense that something is wrong anyway (Melvin, 1996).…”
mentioning
confidence: 99%
“…Some investigations have failed to find ethnic differences in rates of disclosure (Lee & Rotheram-Borus, 2002;Murphy et al, 2001;Schrimshaw & Siegel, 2002), while others have found higher rates among Caucasian families (Armistead et al, 1997;Niebuhr et al, 1993) and/or lower rates among Latina families (Tompkins et al, 1999). Given that previous research examining general disclosure of HIV/AIDS has documented ethnic variation in rates of disclosure (Simoni et al, 1996) and that cultural values may influence the decision to disclose to children in a variety of different ways, it is important to examine whether and how ethnicity may influence disclosure of parental HIV infection to children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown no psychological impact on children (Jones, Foster, Zalot, Chester, & King, 2007;Murphy, Steers, & Stritto, 2001;Shafer, Jones, Kotchick, Forehand, & The Family Health Project Research Group, 2001). Other studies have shown positive effects such as improved parent-child closeness (Gachanja, 2015;Gachanja et al, 2014a;Vallerand et al, 2005), fewer behaviour problems and aggression (Lee & Rotheram-Borus, 2002;Murphy et al, 2001), and an improved outlook on life and the illness (Gachanja, 2015;Gachanja et al, 2014a;Kennedy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown no psychological impact on children (Jones, Foster, Zalot, Chester, & King, 2007;Murphy, Steers, & Stritto, 2001;Shafer, Jones, Kotchick, Forehand, & The Family Health Project Research Group, 2001). Other studies have shown positive effects such as improved parent-child closeness (Gachanja, 2015;Gachanja et al, 2014a;Vallerand et al, 2005), fewer behaviour problems and aggression (Lee & Rotheram-Borus, 2002;Murphy et al, 2001), and an improved outlook on life and the illness (Gachanja, 2015;Gachanja et al, 2014a;Kennedy et al, 2010). Negative effects of full disclosure in children include externalized acting out behaviour problems such as ignoring or arguing with parents (Gachanja, 2015;Murphy, 2008;Vallerand et al, 2005); or internalized problems such as sadness, depression, and withdrawal (Gachanja, 2015;Gachanja et al, 2014a;Kennedy et al, 2010;Petersen et al, 2010;Vallerand et al, 2005).…”
Section: Introductionmentioning
confidence: 99%